TINGKAT PENGETAHUAN REMAJA TENTANG SADARI SEBAGAI DETEKSI DINI KANKER PAYUDARA - Yoenice Josephine Sheren Tambunan; Debilly Yuan Boyoh (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The cause of breast cancer is not known for certain. The disease also has a tendency to be familiar, meaning that a woman with a mother with breast cancer has a greater chance of developing this cancer. This research is a quasi experimental with a Pre Experiment One Group Pre-test Post-test without control design. The population in this study were all adolescent girls in class X at Adevent 1 Jakarta High School as many as 27 respondents. The sample in this study was determined by Non-Probability sampling technique, namely the total sampling method where sampling is equal to the total population. pre test there were 15 (55.5%) respondents who were less knowledgeable, 7 (25.9%) respondents were knowledgeable enough, and 5 (18.6) respondents were well informed. And in the post test all respondents were well informed. The results of the Wilcoxon test obtained a Z value of -4,563 with a p velue of .001 (p 0.05) so that there is an effectiveness of the level of knowledge of adolescent girls about breast cancer and SADARI at SMA Advent 1 Jakarta class X. pretest who had low knowledge were 15 respondents (55.5%), then after being given counseling on breast cancer and SADARI, it can be seen from the results of the posttest that all respondents were well informed, namely 27 respondents (100%).